Doing Participatory Evaluation: from “Jagged World Views” to Indigenous Methodology - Jordan, Steven; Stocek, Christine; Mark, Rodney; Matches, Stacy (The Australian Journal of Indigenous Education, 2009)
Abstract The paper will present findings from a Social Science and Humanities Research (SSHRC) funded participatory evaluation conducted over the past four years in the Cree nation of Wemindji in Quebec, Canada. COOL (Challenging Our Own Limits) or “Nigawchiisuun” in Cree, was launched in 2003 as part of a broader program of governance initiatives within Wemindji. As a key component of this new governance program, COOL was to address the need for after-school care within the community for parents, as well as to engage with the recurring problem of low retention rates in school. In consultation with the Band Council of the Cree Nation of Wemindji (James Bay), the Deputy Chief at the time (Rodney Mark) – who was elected Chief in 2006 – established a COOL committee to oversee the design, organisation, implementation and running of the program. Unlike the other eight Cree communities of the James Bay, Wemindji decided to fund and run its own program based on values, customs, and traditions that have been established through consultations with elders, parents, and other interested groups within the community. This has made COOL a distinctly homegrown, autonomous, self-determined Cree program. The paper will not only report on principal themes and issues connected with the establishment and administration of COOL, but will also discuss why a participatory evaluation has been used to assess its effectiveness as a social/educational program.